2010
DOI: 10.1111/j.1600-9657.2010.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries – knowledge and awareness among present and prospective teachers in selected urban and rural areas of Norway

Abstract: The findings revealed poor knowledge and awareness of TDI among present and prospective teachers in selected parts of Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
(30 reference statements)
4
21
0
3
Order By: Relevance
“…The results of this study showed that the knowledge level of primary school teachers in Ankara is quite low, which is in line with previous studies carried out in other countries (6–15, 24–27).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that the knowledge level of primary school teachers in Ankara is quite low, which is in line with previous studies carried out in other countries (6–15, 24–27).…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have evaluated the knowledge level of schoolteachers with respect to dental trauma and its emergency management (6–15, 24–27). These studies indicate that teachers have a very low level of knowledge about such cases.…”
Section: Discussionmentioning
confidence: 99%
“…The options mentioned in the questionnaire included ice, child's mouth, child's hand and paper/tissue/clean handkerchief. Urban teachers suggested child's hand can be used as the storage/transport media which shows us the lack of knowledge among urban teachers about the storage medium as also noted by Skele,[15] and majority of teachers had preferred "ice" as better storage/transport medium [Table 4b] which can be related to the popular use of ice for transportation of meat, fish or human organs and accidentally detached limbs.…”
Section: Discussionmentioning
confidence: 99%
“…A study undertaken in selected parts of Norway in 2006 revealed poor knowledge and awareness of TDIs among present and prospective teachers. It also documented that information on managing TDIs in schools and educational institutions was scarce and that prospective teachers had not learnt about TDIs in their curriculum.…”
Section: Introductionmentioning
confidence: 99%